Simulation of the dynamic response of steel moment frames following sudden column loss. Experimental calibration of the numerical model and application. Issue 1 (8th February 2018) - Marginean, Ioan; Dinu, Florea; Dubina, Dan
Abstract: Significant research effort has been devoted in recent years to the evaluation of the capacity of steel frame structures to resist progressive collapse after sudden column loss. Due to the complex load‐structure interaction and material behaviour, it can be very difficult to evaluate the ultimate capacity of structural components using current analytical methods. Therefore considerable research effort has been directed to experimental testing and sophisticated numerical simulations. Although sudden column loss is a dynamic process, most experimental studies on full‐scale or scaled down specimens were performed under quasi‐static loads. This paper presents the results of a study devoted to the evaluation of steel frame response following the loss of a column. Advanced numerical models are calibrated using experimental test results and dynamic increase factors are studied. Several full‐scale structures are investigated for a sudden column loss scenario.